Is BTS Different? Shared Episodes on SNS as a Good Indicator for Celebrity Endorsed Ad Effects - Bu, Kyunghee; Kim, Whoe Whun (ASIA MARKETING JOURNAL, 2021)
This study examines the effects of celebrity endorsed advertising from a new perspective of the prior research that emphasizes the matchup between the brand and the celebrity. Due to the recent sharing experiences of the celebrity and their fans on SNS, it is hypothesized that the shared stories would impact viewers’ responses that are often expressed in their likes, dislikes, shares and comments on SNS. In this study, the episodic type of advertising is hypothesized to have more favorable and active responses from viewers than the typical celebrity image-focused ads would have. By crawling and analyzing viewers’ responses on YouTube toward 12 BTS endorsed ads, the hypotheses are confirmed as higher ratio of likes, lower ratio of dislikes and significantly higher ratio of comments over both total views and total likes were found. For the rationale behind, total 1800 comments were categorized into 4 major content types such as attached, experiential, empathic and self-related ones that are all considered as important factors influencing the strong ad effect. The results showed that the episodic ads have marginally more emotional comments than the celeb image ads. The difference was only found in experiential and empathic responses but not in self-related responses. Contrary to the hypothesis, the comments expressing attachment were found more for the celebrity image-focused ads than the episodic ones. It does not seem to suggest that the celebrity image focused ads are better to capture viewers’ attachment towards the celebrity and the ad endorsed, but that the episodic ads draw viewers into relatively deeper level of attachment such as empathy by perceiving the authenticity of the celebrity and the brand. In conclusion, the shared stories on SNS can be a factor in the match-up theory on celebrity endorsed ad effects.